Virtual surgical plan with custom surgical guide for orthognathic surgery: systematic review and meta-analysis - Yoon-Jo Lee; Ji-Hyeon Oh; Seong-Gon Kim (SpringerOpen, 2024)
Abstract Background The shift from traditional two-dimensional (2D) planning to three-dimensional (3D) virtual surgical planning (VSP) has revolutionized orthognathic surgery, offering new levels of precision and control. VSP, combined with computer-aided design/computer-aided manufacturing (CAD/CAM) technology, enables the creation of patient-specific surgical guides and implants that translate preoperative plans into more precise surgical outcomes. This review examines the comparative accuracy and operative efficiency of VSP, especially when used with custom surgical guides, against conventional 2D planning in orthognathic surgery. Main text The study systematically reviewed and analyzed published literature comparing the accuracy and operative time between VSP and conventional planning methods. The meta-analysis included clinical trials, controlled trials, and observational studies on patients undergoing orthognathic surgery, focusing on the degree of alignment between planned and postoperative bone positions and total surgery time. Results indicate that VSP consistently reduces discrepancies between planned and actual surgical outcomes, particularly when integrated with custom surgical guides. Additionally, while VSP demonstrated potential time-saving advantages over conventional planning, these differences were not statistically significant across studies, likely due to high variability among study protocols and designs. Conclusions VSP with custom surgical guides enhances surgical accuracy in orthognathic procedures, marking a significant advancement over traditional methods. However, the reduction in operative time was not conclusively significant, underscoring the need for further studies to evaluate time efficiency. These findings emphasize VSP's role in improving surgical precision, which holds substantial implications for future orthognathic surgical practices.